Broadening the Base, Narrowing the Task: Prioritizing Crop Wild Relative Taxa for Conservation Action. Issue 3 (16th June 2017) - Kell, Shelagh P.; Ford‐Lloyd, Brian V.; Brehm, Joana Magos; Iriondo, José M.; Maxted, Nigel
Abstract : A broad definition of a crop wild relative is any taxon within the same genus as a crop species, or in the case of some crop genepools, other closely related genera. Given the large number of species cultivated for human and animal food, and medicinal, ornamental, environmental, and industrial purposes, the number of taxa related to these crops is inevitably vast, one estimate being >58, 000 species globally. Limited resources for conservation management demands careful planning so that taxa in most urgent need of conservation are given priority. Various prioritization criteria have been used to target wild taxa for conservation action; however, in the case of crop wild relatives, a specific approach is needed to take account of their particular value as potential sources of traits for crop improvement. A surge in conservation planning for crop wild relatives since the turn of the century has resulted in a wide range of different crop wild relative prioritization criteria and methods being applied. This paper reviews those criteria and methods and presents a harmonized, logical, and pragmatic means of assigning priority status to crop wild relative taxa on the basis of three main criteria: (i) the socioeconomic value of crops, (ii) the relative potential value of the wild relatives of socioeconomically valuable crops for variety improvement, and (iii) the relative threat status of the wild relatives of socioeconomically valuable crops.